2019
DOI: 10.1093/molehr/gaz009
|View full text |Cite
|
Sign up to set email alerts
|

Isoform-specific GSK3A activity is negatively correlated with human sperm motility

Abstract: In mouse and bovine sperm, GSK3 activity is inversely proportional to motility. Targeted disruption of the GSK3A gene in testis results in normal spermatogenesis, but mature sperm present a reduced motility, rendering male mice infertile. On the other hand, GSK3B testis-specific KO is fertile. Yet in human sperm, an isoform-specific correlation between GSK3A and sperm motility was never established. In order to analyze GSK3 function in human sperm motility, normospermic and asthenozoospermic samples from adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 64 publications
1
14
0
1
Order By: Relevance
“…Phosphoproteomic (high-performance liquid chromatography-tandem mass spectrometry triple time-offlight) comparison of 2 human sperm subpopulations with high motility (HM) and low motility showed that 40% of phosphoproteins differentially expressed in low motility compared with those in HM were involved in metabolism (44). In the same study, the amount of phospho-Ser21 GSK3a detected by Western blot was significantly higher in human spermatozoa presenting HM, in agreement with a study reporting that total GSK3a and phospho-Ser21 GSK3a levels were lower in human asthenozoospermic samples compared than in normozoospermic ones (45). The significant role played by GSK3a in sperm motility has also been confirmed in mice (46) and goats (47), where this kinase has been found in epididymosomes and its expression to be increased from the caput to the cauda epididymis.…”
Section: Infections and Sperm Motilitysupporting
confidence: 84%
“…Phosphoproteomic (high-performance liquid chromatography-tandem mass spectrometry triple time-offlight) comparison of 2 human sperm subpopulations with high motility (HM) and low motility showed that 40% of phosphoproteins differentially expressed in low motility compared with those in HM were involved in metabolism (44). In the same study, the amount of phospho-Ser21 GSK3a detected by Western blot was significantly higher in human spermatozoa presenting HM, in agreement with a study reporting that total GSK3a and phospho-Ser21 GSK3a levels were lower in human asthenozoospermic samples compared than in normozoospermic ones (45). The significant role played by GSK3a in sperm motility has also been confirmed in mice (46) and goats (47), where this kinase has been found in epididymosomes and its expression to be increased from the caput to the cauda epididymis.…”
Section: Infections and Sperm Motilitysupporting
confidence: 84%
“…A recent report also documents the role for GSK3 and a noncanonical Wnt signaling during epididymal sperm maturation: loss of Wnt signaling in sperm results in male infertility (Koch et al, 2015). The activity of GSK3α isoform has also been correlated with human sperm motility (Freitas et al, 2019). The inability of GSK3β to replace GSK3α, only in testis and sperm, is surprising given the fact that the two isoforms are functionally interchangeable in most cellular contexts and in tissues.…”
Section: Glycogen Synthase Kinase 3α Gsk3α In Spermmentioning
confidence: 99%
“…These observations are compatible with the possibility that mammalian sperm contain a GSK3α-specific binding protein. Efforts to identify a isoform-specific binding protein using a two-hybrid approach with testis cDNA yielded a number of GSK3 binding proteins, but these GSK3 interactors were not isoform specific (Freitas et al, 2019). However, a yeast two-hybrid approach using human fetal cDNA yielded four GSK3α-specific binding proteins one of which appears to play a role in regulating circadian rhythm (Zeidner et al, 2011).…”
Section: The Proteins Pp1γ2 Gsk3α Pka Cα2 and Ppp3r2/cc Present Onmentioning
confidence: 99%
“…It is now well recognized that the GSK3α enzyme plays an important role in the acquisition of sperm motility and acrosomal reaction in mammals (55)(56)(57). The inhibitory GSK3α S21 phoshorylation is high during the epididymal sperm maturation stage, but subsequently decreases to activate the kinase activity during the hyperactivation phase in the female oviduct (58)(59)(60)(61). This latter mammalian hyperactivation mechanism is reminiscent of the activation of motility in marine fish spermatozoa (31), which is also associated with the dephosphorylation of GSK3α S21 as demonstrated here in the seabream.…”
Section: Discussionmentioning
confidence: 99%